Development of a Digital Bullying Behavior Screening Instrument (Web/Mobile) for School Counselors: Validity, Reliability, and Feasibility Evaluation - Aslinda; Dinda Dwi Purnama Mursalin; Dwi Muslimah Angraeni; Delavia Pabalik; Awanda Erna; Indah Puteri (Jurusan Teknik Informatika dan Komputer, 2024)
This study aimed to develop and validate a digital bullying screening instrument (DBSI) for school counselors to detect, assess, and monitor bullying behaviors among students. While traditional paper-based instruments have limitations in real-time monitoring and scalability, a web/mobile platform provides faster, more reliable, and accessible tools for early intervention and data-driven counseling. The study addresses the research gap in digital assessment tools that integrate psychometric validity, usability, and practical feasibility in school settings. A mixed-methods approach was employed. The study included 350 students from urban and suburban schools, selected using stratified random sampling. The instrument was developed based on literature review and expert consultation, followed by content validation, pilot testing, and refinement. Psychometric properties, including internal consistency (Cronbach’s α), test-retest reliability (ICC), and construct validity, were assessed. Usability and feasibility were evaluated through surveys and structured interviews with school counselors. Statistical analyses included exploratory and confirmatory factor analysis, descriptive statistics, and correlation analysis. The DBSI demonstrated high internal consistency (α = 0.89), stable test-retest reliability (ICC = 0.87), and a three-factor structure representing verbal, social/relational, and cyberbullying behaviors. Counselors reported the instrument as easy to use, time-efficient, and supportive of intervention planning. Prevalence data highlighted cyberbullying as the most common form among participants, consistent with previous research.The study confirms that digital tools enhance the efficiency and effectiveness of school-based bullying assessments, supporting early detection and targeted interventions. Limitations include sample restriction, self-report bias, and short-term implementation, which may constrain generalizability. The DBSI offers a validated, scalable, and technology-integrated solution for school counselors. Future research should investigate long-term intervention outcomes and adaptation for rural or low-connectivity contexts.